2018
DOI: 10.1159/000495086
|View full text |Cite
|
Sign up to set email alerts
|

Global mRNA and Long Non-Coding RNA Expression in the Placenta and White Adipose Tissue of Mice Fed a High-Fat Diet During Pregnancy

Abstract: Background/Aims: Gestational diabetes mellitus (GDM) is a common complication of pregnancy, but the mechanisms underlying the disorders remain unclear. The study aimed to identify mRNA and long non-coding RNA (lncRNA) profiles in placenta and gonadal fat of pregnant mice fed a high-fat diet and to investigate the transcripts and pathways involved in the development of gestational diabetes mellitus. Methods: Deep and broad transcriptome profiling was performed to assess the expression of mRNAs and lncRNAs in pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Mice with targeted disruption in the gene for Elovl6 (Elovl6 –/–) are resistant to diet-induced insulin resistance ( 42 ). Huang et al demonstrated that Actg2, Cnfn, Muc16, and Serpina3k are at the gene network core in the placental tissue and that the genes Tkt, Acss2, and Elovl6 served as the network core in the gonadal fat tissue for mice with an HF diet ( 43 ). In our study, Elovl6 gene expression was greatly repressed in the placenta of the rats with an HF diet.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with targeted disruption in the gene for Elovl6 (Elovl6 –/–) are resistant to diet-induced insulin resistance ( 42 ). Huang et al demonstrated that Actg2, Cnfn, Muc16, and Serpina3k are at the gene network core in the placental tissue and that the genes Tkt, Acss2, and Elovl6 served as the network core in the gonadal fat tissue for mice with an HF diet ( 43 ). In our study, Elovl6 gene expression was greatly repressed in the placenta of the rats with an HF diet.…”
Section: Discussionmentioning
confidence: 99%
“…There are few reports on CNFN, and no reports verifying its function, to the best of our knowledge. Huang et al (37) revealed that CNFN was one of the core genes in the placental tissue involved in the development of gestational diabetes mellitus. Michibata et al (38) demonstrated that CNFN had increased expression in psoriatic skin.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA transcripts were analyzed after using GCBI to filter out genes with detection rates below 50% in the overall expression profile. The mRNAs between the comparison groups exhibited expression fold-changes ≥ 2 and p -values ≤ 0.01, which were considered significant ( Huang et al, 2018 ). Gene set enrichment analysis (GSEA) was conducted on the desktop version of the GSEA software (v.4.1.0).…”
Section: Methodsmentioning
confidence: 99%